Hairy Cell Leukemia Presenting with Isolated Skeletal Involvement Successfully Treated by Radiation Therapy and Cladribine: A Case Report and Review of the Literature - Yonal-Hindilerden, Ipek; Hindilerden, Fehmi; Bulut-Dereli, Sanem; Yıldız, Eren; Dogan, Ibrahim Oner; Nalcaci, Meliha (Case Reports in Hematology, 2015)
We describe an unusual case of hairy cell leukemia (HCL) in a 55-year-old male presenting with isolated skeletal disease as the initial manifestation without abnormal peripheral blood counts, bone marrow involvement, or splenomegaly. To the best of our knowledge, there have been only two previous reports of a similar case. The patient presented with pain in the right femur. Anteroposterior radiographs of both femurs revealed mixed lytic-sclerotic lesions. PET scan showed multiple metastatic lesions on axial skeleton, pelvis, and both femurs. Histopathological examination of the bone biopsy revealed an infiltrate of HCL. Localized radiation therapy to both proximal femurs and subsequently 4 weeks later, a 7-day course of 0.1 mg/kg/day cladribine provided complete remission with relief of symptoms and resolution of bone lesions. We addressed the manifestations and management of HCL patients with skeletal involvement.